Factors Influencing Costumers Buying Intention for Housing Unit in Depok - Maoludyo, Faishal Tanjung; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abtract. Housing demand and supply in Jakarta is not balanced with the situation in greater demand. This makes the price of land rises. For those who can not afford to buy a home should choose to live in cities buffers such as Bogor, Depok, Tangerang, and Bekasi. Data indicate if Depok has the lowest land prices and the most to be the target, buyers. To take advantage of these opportunities, housing developers must know the characteristics of prospective homebuyers in Depok. This research will seek consumer behavior in buying a home in Depok.The basis of this study using input phase and the phase of the process. Input phase consists of marketing efforts by companies and social state of the environment. In the marketing efforts include marketing mix (4P) and the state of the state of the social environment includes influential people in buying property. In the phase of the process consists of awareness needs, information search, and evaluation options. The research will use questionnaires Both will be asked to use a Likert scale and with a nominal cross-sectional method. Once the data is collected, the data will be analyzed using descriptive analysis. Results indicate if the personal decision as important as the decision of the couple. They buy because of the urgent decision to stay. The sources of information used are the newspapers, the Internet, friends, and exhibition. And among many factors, the price factor is the most important factor.Â Keywords:Real Estate, Consumer Decision Making Process, Marketing Mix, Buffer City